Primary intracranial myxoid chondrosarcoma: report of a case and review of the literature. - Im, So-Hyang (Korean Academy of Medical Sciences, 2003)
The authors present a case of primary intracranial extraosseous myxoid chondrosarcoma without any attachment to the cranium or the meninges. The clinical and radiological findings of the primary intraparenchymal tumor are described with a review of the literature concerning cranial and intracranial myxoid chondrosarcoma.